2018
DOI: 10.1080/19491034.2017.1419112
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous transcription

Abstract: Numerous studies based on new single-cell and single-gene techniques show that individual genes can be transcribed in short bursts or pulses accompanied by changes in pulsing frequencies. Since so many examples of such discontinuous or fluctuating transcription have been found from prokaryotes to mammals, it now seems to be a common mode of gene expression. In this review we discuss the occurrence of the transcriptional fluctuations, the techniques used for their detection, their putative causes, kinetic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 118 publications
1
11
0
Order By: Relevance
“…After this procedure, the total transcription signal in the nucleoplasm showed symptoms of fluctuations with two discernible, though not very distinct, peaks (Fig 6). Evaluating these results, we have to keep in mind that various nucleoplasmic genes in the same cell display a wide range of transcriptional kinetic behavior (reviewed in Smirnov et al [1]). [4, 10, 55, 56] Moreover, some of these genes are expressed in typical bursts with long periods of silence, during which they cannot be detected by FU incorporation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After this procedure, the total transcription signal in the nucleoplasm showed symptoms of fluctuations with two discernible, though not very distinct, peaks (Fig 6). Evaluating these results, we have to keep in mind that various nucleoplasmic genes in the same cell display a wide range of transcriptional kinetic behavior (reviewed in Smirnov et al [1]). [4, 10, 55, 56] Moreover, some of these genes are expressed in typical bursts with long periods of silence, during which they cannot be detected by FU incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that genes in all kinds of organisms, from prokaryotes to mammals, can be transcribed in short bursts or pulses alternated by periods of silence (reviewed in Smirnov et al [1]) The probability of such mode of expression was suggested long ago;[2] now it seems that the discontinuous transcription is a common feature of the gene expression, at least in mammalian cells. [312] The periodical switches of the promoter between the active and “refractory” states may be crucial in the efficient regulation of the gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies show that genes in all kinds of organisms, from prokaryotes to mammals, can be transcribed in short bursts or pulses alternated by periods of silence (reviewed in Smirnov et al [1]) The probability of such mode of expression was suggested long ago; [2] now it seems that the discontinuous transcription is a common feature of the gene expression, at least in mammalian cells. [3][4][5][6][7][8][9][10][11][12] The periodical switches of the promoter between the active and "refractory" states may be crucial in the efficient regulation of the gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…[9] A spontaneous heterogeneity of gene expression occasioned by transcriptional fluctuations may influence cell behaviour in changing environmental conditions and in the course of differentiation. [18] The discontinuous character of transcription has been detected by various methods (reviewed in Smirnov et al [1]) The number of transcripts produced in a certain (sufficiently short) period of time may be determined with high precision by single molecule RNA fluorescence in situ hybridisation (smFISH). [19][20][21] The results of such quantification alone provide indirect, but valuable information for modelling the expression kinetics in a cell population or tissue, when the studied gene is supposed to be transcriptionally active in all the cells.…”
Section: Introductionmentioning
confidence: 99%